Analysis of low power wide area network wireless technologies in smart agriculture for large-scale farm monitoring and tractor communications. (January 2022) - Klaina, Hicham; Guembe, Imanol Picallo; Lopez-Iturri, Peio; Campo-Bescós, Miguel Ángel; Azpilicueta, Leyre; Aghzout, Otman; Alejos, Ana Vazquez; Falcone, Francisco
Highlights: Large-scale farm monitoring assessment of LPWAN with tractor/farmer interaction. Wireless channel analysis of multiple communication links in the farming scenario. Coverage/capacity analysis enhancing equipment performance and resource management. LPWAN-based WSNs provide in general enhanced communication performance. System validation, providing flexible/ scalable solutions for interactive farming. Abstract: In this paper, the assessment of multiple scenario cases for large-scale farm monitoring using Low-Power Wide-Area Network (LPWAN) based near-ground sensor nodes with the interaction of both tractors and farmers are presented. The proposed scenario under analysis considers multiple communication links, namely nodes to infrastructure, nodes to tractor, nodes to farmer, tractor to infrastructure and farmer to infrastructure communications. Moreover, these scenarios are proposed for tractors and agricultural equipment performance improvement and tracking, as well as resources management within the farm field. Different link type configurations are tested in order to consider the impact of ground, spatial distribution as well as infrastructure elements. The results show that LPWAN-based WSNs can provide better performance in terms of coverage and radio link quality results than ZigBee for a non-flat large-scale farm field in both cases of near-ground fixed nodes and moving tractor and farmer. The proposed systems are validated by cloud-based platforms for LoRaWAN, Sigfox and NB-IoT communications, providing flexible and scalable solutions to enable interactive farming applications.